Variabel Yang Memengaruhi Keberhasilan Wirausaha Pemula Di DIY - Ariani, Dorothea Wahyu; Susilo, Yuvensius Sri; Herawan, Jonathan Ersten (Jurnal Maksipreneur, 2023)
This study aims to conduct a study of novice entrepreneurs in Yogyakarta. This study analyzes the amount of capital, the number of employees, the length of time running the business, the age of the entrepreneur, education (graduated from bachelor's degree or high school), and whether the business is a legal entity or not. This study used 335 novice entrepreneurs who filled out a questionnaire followed by in-depth interviews with ten willing novice entrepreneurs. Focus group discussions were also conducted with related sources. The analytical tools used in this research are descriptive analysis and ordinary least squares (OLS). The results showed that the amount of capital and the number of employees affected sales or business income, but the variables of business length, entrepreneurial age, and level of education had no significant effect on sales or business income. In general, the results of this study indicate that there are still various problems in running a business, especially regarding the problem of product marketing and social capital owned by novice entrepreneurs in Yogyakarta.